The impact of terrorism on economic performance: The case of Turkey - Ruiz Estrada, Mario Arturo; Park, Donghyun; Khan, Alam (Elsevier, 2018)
We apply the terrorist attack vulnerability evaluation model (TAVE-Model) to evaluate the effect of terrorism on the economic performance of Turkey. We examine both the short run and long-run economic impact of terrorist attacks in Turkey. The TAVE-Model deploys a number of indicators to evaluate the economic impact. The indicators are economic desgrowth (-δ), intensity of terrorist activities (αi), terrorist attack losses (-π), economic wear (Π), level of terrorist attack tension (ζ), level of terrorist attacks monitoring (η), and total economic leaking (Ωt) under a terrorist attack. The basic underlying idea of TAVE-Model is that the economic impact of a terrorist attack depends on a country's vulnerability to attacks from domestic and international terrorist groups. The application of a model to Turkey is highly topical in light of the spate of terrorist attacks the country suffered in recent years. The results of TAVE-Model confirm that economic leaking, economic desgrowth, and economic wear has increased between 1990 and 2016. The issue of terrorism in Turkey is multidimensional, and tackling it requires an effective social assistance program as well as a stronger and impartial justice system. These reforms will render poorer Turks less vulnerable and increase the opportunity cost of terrorism.